Pengaruh Pemanfaatan TikTok Terhadap Pemenuhan Kebutuhan Informasi Kecantikan Mahasiswa Tata kecantikan Universitas Negeri Semarang (Beauty and Beauty Health Education, 2023)
Abstract. Tiktok is one of the most popular social media used, its popularty started in 2020 and increasing every year with the most users from generation Z. TikTok offers a variety of content, ranging from content that provides entertainment, information, education and even persuasion, where content in the beauty category is ranked third out of the five most watched video categories. Beauty content on social media tiktok can also be a source of knowledge for people who study about beauty science, as is the case for students of beauty education study programs who can make beauty content on tiktok social media a source of fulfilling information needs about beauty as they study. in college. The purpose of this study is to find out the effect of utilizing tiktok social media on fulfilling the beauty information needs of beauty education students Semarang University. The approach to this research is descriptive quantitative with the Utilization of Social Media TikTok as the independent variable (X) and the Beauty Information Needs of beauty education Students, Semarang University as the dependent variable (Y). Data collection was carried out using a survey method, with a causal research design. The population in this study were active students of the beauty education study program force of the year 2019 and 2018 with a total of 118 students, of which the 2019 class consisted of 58 students and the 2018 class with 60 students. The results of the study show that there is a significant positive influence between the use of social media TikTok on fulfilling the needs for beauty information in beauty education Students at Semarang State University. From the calculation results it can be concluded that the influence of variable X on variable Y is 83% and the remaining 17% is from other factors not examined by researchers in this study. Abstract. TikTok menjadi media sosial populer yang menyuguhkan beragam macam konten, mulai dari konten yang sifatnya memberikan hiburan, informasi, edukasi bahkan persuasif, di mana konten dengan kategori kecantikan masuk kedalam peringkat ketiga dari lima kategori video yang paling banyak ditonton. Konten kecantikan di sosial media tiktok tersebut dapat menjadi sumber pengetahuan bagi orang-orang yang mendalami ilmu kecantikan, seperti halnya bagi mahasiswa program studi pendidikan tata kecantikan yang dapat menjadikan konten kecantikan pada media sosial tiktok sebagai sumber pemenuhan kebutuhan informasi tentang kecantikan sebagaimana yang mereka dalami di bangku kuliah. Peneliti tertarik untuk melihat lebih jauh tentang bagaimana “Pengaruh Pemanfaatan Media Sosial Tiktok Terhadap Pemenuhan Kebutuhan Informasi Kecantikan Mahasiswa Tata Kecantikan Universitas Negeri Semarang”. Pendekatan penelitian menggunakan deskriptif kuantitatif dengan Pemanfaatan Media Sosial TikTok sebagai variabel independen/bebas (X) dan Kebutuhan Informasi Kecantikan Mahasiswa Tata Kecantikan Universitas Negeri Semarang sebagai variabel dependen/terikat (Y). Pengumpulan data dilakukan dengan metode survey, dengan desain penelitian Kausal. Populasi penelitian 91 mahasiswa aktif program studi tata kecantikan angkatan 2019 dan 2018. Hasil penelitian menunjukkan terdapat pengaruh signifikan positif antara pemanfaatan media sosial TikTok terhadap pemenuhan kebutuhan informasi kecantikan pada mahasiswi tata kecantikan Universitas Negeri Semarang. Hasil perhitungan dapat disimpulkan adanya pengaruh variabel X terhadap variabel Y sebesar 83% dan selebihnya 17% dari faktor lain yang tidak diteliti peneliti dalam penelitian ini.